Android-Based National Examination: Honest Character Applicator - Santi Vera Mulyani; Nurhayati Nurhayati; Mohd Hilmy Baihaqy Yussof (Universitas Bengkulu, 2020)
This research originated from concerns about the opportunity to cheat if the test was conducted on computer media and smartphones (Android). This study aimed at determining the process of implementing computer-based and Android-based National Examination (USBN), constraints that may be faced, whether or not there are opportunities for examinees to cheat, effective or not, and whether or not USBN-based and computer-based USBN is efficient. In this study, researchers used descriptive research methods by collecting data on interviews, documents, and library sources as primary data sources and secondary data. The implementation of USBN CBT (National Standard School Exams Based Test) is an alternative in minimizing paper use. USBN CBT is more effective and efficient than USBN PBT (Paper Based Test). The results of the study found that: the process and technical implementation of computer-based and android-based USBN in 9 high schools throughout the Banyuasin District of South Sumatra Province differed from one another, 2) There were no severe constraints, 3) There was no opportunity for exam participants to cheat, 4) Very effective because it is easier to practice, 5) Very efficient because it can minimize the use of paper and electricity, especially in USBN based on Android. In the following years, it was strongly recommended to implement computer-based and android-based USBN both in the high school environment throughout the Banyuasin District, in South Sumatra and throughout Indonesia in general.